2004
DOI: 10.1038/sj.cdd.4401449
|View full text |Cite
|
Sign up to set email alerts
|

Mice overexpressing human caspase 3 appear phenotypically normal but exhibit increased apoptosis and larger lesion volumes in response to transient focal cerebral ischaemia

Abstract: Caspase 3 activation has been implicated in cell death following a number of neurodegenerative insults. To determine whether caspase genes can affect the susceptibility of cells to neurodegeneration, a transgenic mouse line was created, expressing human caspase 3 under control of its own promoter. The human gene was regulated by the murine homeostatic machinery and human procaspase 3 was expressed in the same tissues as mouse caspase 3. These novel transgenic mice appeared phenotypically and developmentally no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 72 publications
(91 reference statements)
0
18
0
Order By: Relevance
“…In transgenic mice, overexpression of the human caspase-3 gene did not induce morphogenetic defects during normal development but leads to greater apoptosis under stress conditions (Kerr et al, 2004). The transgenic mice showed significantly larger lesions when they were subjected to focal cerebral ischaemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 92%
“…In transgenic mice, overexpression of the human caspase-3 gene did not induce morphogenetic defects during normal development but leads to greater apoptosis under stress conditions (Kerr et al, 2004). The transgenic mice showed significantly larger lesions when they were subjected to focal cerebral ischaemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 92%
“…We therefore examined the role of nucleophosmin in vivo using a mouse model of stroke. Previous data from our laboratory (Kerr et al, 2004b) and many others (Matsushita et al, 1998;Cao et al, 2001) have demonstrated Bax involvement in the apoptotic cell death that occurs following experimental transient occlusion of the MCA. Bax translocation has also been reported in both rats (Cao et al, 2001) and mice (Gao et al, 2005) using this model.…”
mentioning
confidence: 73%
“…Monofilament occlusion of the MCA was performed in adult male mice (25-30 g, approximately 10-12 weeks) as described previously (Kerr et al, 2004b). Animals were subjected to 30 min of ischaemia and killed at 3, 6, 12 and 24 h by trans-cardiac perfusion with 4% paraformaldehyde under deep anaesthesia (pentobarbitone, 60 mg/kg intraperitoneally).…”
Section: Proximity Assaymentioning
confidence: 99%
“…Furthermore, serum withdrawal, which induced the repression of Dicer expression, indeed increased the expression of caspase-3. It has been reported that mice overexpressing caspase-3 are phenotypically normal under physiological conditions, while exhibiting increased apoptosis in response to ischemia-reperfusion injury, implying the role of an increased expression of caspase-3 in the increased susceptibility to degenerative insults (23). These results indicated the causative role of Dicer repression in caspase-3 upregulation in response to serum withdrawal and suggested that the upregulation of caspase-3 in the settings of Dicer downregulation involves an increased sensitivity to apoptosis.…”
Section: Discussionmentioning
confidence: 99%